Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/jcpt.13792
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of bronchoalveolar lavage fluid galactomannan assay for invasive pulmonary aspergillosis in adults: A meta‐analysis

Abstract: What is known and objective: To analyse the diagnostic accuracy of bronchoalveolar lavage fluid galactomannan (BALF-GM) assay for invasive pulmonary aspergillosis (IPA) in adults to determine the optimal diagnostic cut-off by meta-analysis.Methods: PubMed, Embase, Web of Science, Cochrane Library, China national knowledge infrastructure (CNKI), and China Wanfang databases were searched to collect relevant studies on the diagnostic value of BALF-GM for IPA from inception to March 2022. The summary receiver oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The cut-off for positivity in serum is still controversial: single value over 0.5 is recommended by the manufacturer, while experts suggest a cut-off over 0.7 for a single test or two consecutive tests > 0.5 [ 119 ]. In BALF too, there is no consensus between >0.5 and >1.0, although a recent meta-analysis including 19 articles concluded in favor of the >0.5 cut-off associated with a sensitivity of 89% and a specificity of 79% [ 120 ].…”
Section: Microbiological Findingsmentioning
confidence: 99%
“…The cut-off for positivity in serum is still controversial: single value over 0.5 is recommended by the manufacturer, while experts suggest a cut-off over 0.7 for a single test or two consecutive tests > 0.5 [ 119 ]. In BALF too, there is no consensus between >0.5 and >1.0, although a recent meta-analysis including 19 articles concluded in favor of the >0.5 cut-off associated with a sensitivity of 89% and a specificity of 79% [ 120 ].…”
Section: Microbiological Findingsmentioning
confidence: 99%
“…Only 37.3% (19/51) of the serum GM tests were positive in patients diagnosed with IPA in this study. Moreover, 46.8% (15/32) of those who received antifungal treatment before GM test .The results of our study demonstrated that BALF is the optimal specimen for Aspergillus culture and GM test [14] . But there was no significant difference in the levels of anti-Aspergillus antibodies between the two groups.…”
Section: Discussionmentioning
confidence: 66%
“…The classical imaging features of IPA embrace air crescent, halo, cavitation, and nodule. However, a study of 72 proven cases of IPA found that non-vascular invasion signs, such as nonspecific infiltrates and consolidation, were more commonly observed (68.1% and 38.9% respectively) than typical signs [13] .The delay in diagnosis IPA lead to treatment delays, thus increasing the morbidity and mortality of IPA, which is more common in patients with nonimmunosuppressive diseases [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BALF ODI 1.0 pooling resulted in a sensitivity of 0.75 and a specificity of 0.96 [ 44 ]. Moreover, in another meta-analysis, it was shown that the AUCs were 0.92, 0.86, 0.93, 0.89, 0.88, and 0.94 when the cut-off values were 0.5, 0.8, 1.0, 1.5, 2.0, and 3.0, respectively [ 48 ]. For the other factors, differences in diagnostic levels of the different variables were explored by regression in the heterogeneity assessment, where neutropenia and consecutive sampling significantly affected the sensitivity of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%